Starch metabolism in potato Solanum tuberosum L. - E. M. Sergeeva; K. T. Larichev; E. A. Salina; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Starch is a major storage carbohydrate in plants. It is an important source of calories in the human and animal diet. Also, it is widely used in various industries. Native starch consists of water-insoluble semicrystalline granules formed by natural glucose polymers amylose and amylopectin. The physicochemical properties of starch are determined by the amylose:amylopectin ratio in the granule and degrees of their polymerization and phosphorylation. Potato Solanum tuberosum L. is one of the main starch-producing crops. Growing industrial needs necessitate the breeding of plant varieties with increased starch content and specified starch properties. This task demands detailed information on starch metabolism in the producing plant. It is a complex process, requiring the orchestrated work of many enzymes, transporter and targeting proteins, transcription factors, and other regulators. Two types of starch are recognized with regard to their biological functions. Transitory starch is synthesized in chloroplasts of photosynthetic organs and degraded in the absence of light, providing carbohydrates for cell needs. Storage starch is synthesized and stored in amyloplasts of storage organs: grains and tubers. The main enzymatic reactions of starch biosynthesis and degradation, as well as carbohydrate transport and metabolism, are well known in the case of transitory starch of the model plant Arabidopsis thaliana. Less is known about features of starch metabolism in storage organs, in particular, potato tubers. Several issues remain obscure: the roles of enzyme isoforms and different regulatory factors in tissues at various plant developmental stages and under different environmental conditions; alternative enzymatic processes; targeting and transport proteins. In this review, the key enzymatic reactions of plant carbohydrate metabolism, transitory and storage starch biosynthesis, and starch degradation are discussed, and features specific for potato are outlined. Attention is also paid to the known regulatory factors affecting starch metabolism.